Synergetic effect of grain size reduction on electronic and thermal transport properties by selectively-suppressed minority carrier mobility and enhanced boundary scattering in Bi0.5Sb1.5Te3 alloys. (February 2019) - Lee, Kyu Hyoung; Shin, Weon Ho; Kim, Hyun-Sik; Lee, Kimoon; Roh, Jong Wook; Yoo, Joonyeon; Kim, Ji-il; Kim, Sung Wng; Kim, Sang-il
Abstract: Controlling electronic and thermal transport properties simultaneously is an ultimate strategy to accomplish high-performance thermoelectrics. Here, our analysis on carrier transport of a nanograined p-type Bi0.5 Sb1.5 Te3 thermoelectric alloy clearly reveals that reducing grain size greatly suppresses bipolar conduction by selective suppression of minority carrier (electron) mobility, resulting in both the power factor enhancement and bipolar thermal conductivity reduction. Furthermore, it is shown how reducing grain size affects decreasing lattice thermal conductivity in respect to grain size and phonon wavelength. Therefore, minimizing grain size can enhance thermoelectric performance of Bi0.5 Sb1.5 Te3 alloy by controlling both electronic and thermal transport properties synergetically. Graphical abstract: